WATSON WAVELET TRANSFORM: CONVOLUTION PRODUCT and TWO-WAVELET MULTIPLIERS - Upadhyay S.K.; Shukla P. (My University, 2025)
In this paper, utilizing the theory of Watson transform and Watson convolution, we explore the Watson wavelet convolution product and its related properties. The relation between the Watson Wavelet convolution product and Watson convolution is also computed. Watson wavelet transform and its inversion formula are analyzed heuristically. Watson two-wavelet multipliers and its trace class are derived from Watson wavelet convolution product. © 2023 The Author(s).